Educational research networks principles of organization. - N. Davydova, Nataliia; M. Dorozhkin, Evgeniy; A. Fedorov, Vladimir (International Journal of Engineering and Technology, 2018)
Relevance. Modern society has global transformations; as a result, the level characteristics of its system development are changing, new opportunities and new situations to implement a self-organizing system to solve problems of self-government appear. Thus, there is the need to organize the multiplicity of interactions in the new environment, including education. The success of the development mechanisms, organizing innovative activities in the educational systems of different levels is largely determined by the active development of interaction network forms and interaction effective management. The article is devoted to development of theoretical ideas about the processes of network interaction in education to justify and describe the principles of modern scientific-educational network on the basis of system-synergetic approach. A leading approach to study this problem can be considered as system-synergetic which allows studying network interaction within the scientific and educational network as a holistic entity consisting of interrelated elements, structured and complex. The results of the study showed that described principles of effective networking and the conditions of scientific and educational networks development allow you to combine and re-combine the accumulated actors of this knowledge and practical experience interaction, turning them into the means of its innovative activities. The article can be useful to heads of educational institutions of different levels, as well as researchers of innovative processes development problems in education. Â